Cloning and sequence analysis of cDNA for human argininosuccinate lyase. - W E O'Brien; Roderick R. McInnes; K. E. Kalumuck; M Adcock (1986)
Using antibodies specific for argininosuccinate lyase (EC 4.3.2.1), we isolated two cDNA clones by screening a human liver cDNA library constructed in the lambda gt11 expression vector. The identity of these isolates was confirmed by in vitro translation of plasmid-selected mRNA. One of these isolates was used to rescreen the cDNA library and a 1565-base-pair (bp) clone was identified. The entire nucleotide sequence of this clone was determined. An open reading frame was identified which encoded a protein of 463 amino acids with a predicted molecular weight of 51,663. The clone included 115 bp of 5' untranslated sequence and 46 bp of 3' untranslated sequence. A canonical poly(A) addition site was present in the 3' end, 16 bp from the beginning of the poly(A) tract. Comparison of the deduced amino acid sequence of the human enzyme with that of the yeast enzyme revealed a 56% homology, when conservative amino acid changes were taken into consideration. The yeast protein is also 463 amino acids long, with a molecular weight of 51,944. By use of a genomic DNA panel from human-Chinese hamster somatic cell hybrids, the human gene was mapped to chromosome 7. Another hybridizing region, corresponding to a portion of the 5' end of the cDNA, was found on chromosome 22.